Analisis Hukum Ekonomi Syariah terhadap Perubahan Nisbah Bagi Hasil Secara Sepihak pada Akad Mukhabarah Studi di Kelurahan Tanjung Senang Bandar Lampung - Asih Nugraheni; Sucipto Sucipto; Helma Maraliza (Fakultas Syariah IAIN Kerinci, 2026)
This study analyzes the compatibility of the profit-sharing (bagi hasil) practice between tenant farmers and landowners in Tanjung Senang Village, with the mukhabarah contract under Sharia Economic Law, and to formulate a dual-normative legal resolution model as legal protection for tenant farmers who suffer losses. This study uses a descriptive qualitative field-research method. The main instrument was an in-depth interview guide for a landowner and a tenant farmer as informants, supplemented by field observation, while secondary data were drawn from fiqh al-muamalah literature and relevant journal articles. Data were analyzed inductively through data reduction, presentation, and conclusion drawing and verification. The results show that the practice fulfills the pillars (rukun) of the mukhabarah contract, but its implementation is defective: a verbal 1:2 ratio (one share for the landowner, two for the tenant farmer) was unilaterally changed by the landowner to 1:1 at harvest time, without prior consultation, violating an-taradhin (mutual consent), al-'adl (justice), and wafa' bil 'uqud (fulfillment of contracts), and breaching 'urf shahih (valid custom), since the 1:2 ratio holds a status equal to an agreed contractual condition. This study concludes that the practice is conceptually permissible in Islam, but its implementation deviates from Sharia Economic Law due to the absence of a written agreement and the unilateral change of ratio. A dual-normative resolution model is proposed, synchronizing the Compilation of Sharia Economic Law (KHES) with Law No. 2 of 1960, combining administrative certainty via registered written agreements with substantive justice via recognition of 'urf shahih.